HUBUNGAN SCHOOL WELL-BEING DENGAN KEMATANGAN EMOSI SISWA GENERASI Z DI SMA NU 2 GRESIK - Al Farabi, Nur Muhammad; Shobihah, Ida Fitri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
The learning environment of students is one of the factors that influence their emotional maturity. School well-being refers to a school condition that enables individuals to fulfil their basic needs, including having, being, and health. This study aims to examine the relationship between school well-being and the emotional maturity of Generation Z students at SMA NU 2 Gresik. This research employs a quantitative method. The study population consists of 270 students, with a research sample of 68 students selected using simple random sampling. Data analysis was conducted using a parametric technique, specifically Pearson’s product-moment correlation. The results show a correlation coefficient of 0.365 with a significance level of 0.002, indicating a positive relationship between school well-being and emotional maturity. The higher the level of school well-being, the higher the students’ emotional maturity. These findings imply that efforts to improve student well-being at school, through strengthening physical, social, and emotional environments, can serve as a vital strategy in supporting healthy emotional development among adolescents, particularly those from Generation Z.